Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fimmu.2016.00574
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Regulatory T Cells: Exosome- and Non-Coding RNA-Mediated Regulation of Homeostasis and Resident Treg Cells

Abstract: Regulatory T (Treg) cells are a group of cells that are heterogeneous in origin and in functional activity. Treg cells comprise a necessary balance to adaptive immune responses. As key regulators of self-tolerance, Treg cells have been involved in a series of pathologic processes and considered as therapeutic targets. Here, we summarize recent research regarding Treg cell origins and their functional classification, highlight the role of exosomes and non-coding RNA in modulating Treg cell homeostasis, and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 100 publications
0
36
0
1
Order By: Relevance
“…Accumulating evidence has revealed that exosomes and ncRNAs (miRNA and lncRNA) are critical to Treg cell homeostasis (103). For example, tumour exosomal miRNAs may induce immune tolerance and then exert an adverse immune effect (104).…”
Section: Exosomal Circrnas Promote the Generation Of Premeta-mentioning
confidence: 99%
“…Accumulating evidence has revealed that exosomes and ncRNAs (miRNA and lncRNA) are critical to Treg cell homeostasis (103). For example, tumour exosomal miRNAs may induce immune tolerance and then exert an adverse immune effect (104).…”
Section: Exosomal Circrnas Promote the Generation Of Premeta-mentioning
confidence: 99%
“…Exosomes contain a wide variety of proteins, lipids, RNAs, non-transcribed RNAs, miRNAs, and small RNAs (Yin et al, 2013;Becker et al, 2016). Ongoing efforts have shown that miRNAs are secreted into tumor microenvironments to regulate cancer cell proliferation, migration, immune response, intercellular communication, and stromal modification, thereby promoting tumor growth and progression (Meckes et al, 2010;Zhang et al, 2015b;Li et al, 2016). EBV-regulated miRNAs and viral proteins can be secreted in exosomes to regulate the tumor microenvironment.…”
Section: Ebv Regulates the Inflammatory Tumor Microenvironment Via MImentioning
confidence: 99%
“…Immune homeostasis is established by production of immune suppressive cytokines such as IL10 and transforming growth factor-β (TGFβ). 63,64 As sarcoidosis has many elements resembling a deregulated immune response, impaired function of Tregs may be a possible contribution factor to the response seen in sarcoidosis. Indeed, an impaired suppressive function of peripheral Tregs from sarcoidosis patients has been observed in several studies.…”
Section: Regulatory T Cellsmentioning
confidence: 99%